Roles of fibroblasts from the interface zone in invasion, migration, proliferation and apoptosis of gastric adenocarcinoma. Issue 10 (26th July 2012) - Shan, Li-Hui; Sun, Wen-Guang; Han, Wei; Qi, Lei; Yang, Chun; Chai, Cui-Cui; Yao, Ke; Zhou, Qiu-Feng; Wu, Hong-Mei; Wang, Li-Feng; Liu, Jia-Ren
Abstract : Aims: Interface zone fibroblasts (INFs) are very important in the progression and metastasis of tumours but their effect on the invasion and migration of gastric cancer cells is still unclear. Methods: Primary fibroblasts were isolated from the distal normal zone (normal zone fibroblasts, NFs), interface zone (INFs) and tumour zone (cancer-associated fibroblasts, CAFs) of 60 human gastric carcinoma tissue samples. The crosstalk between these fibroblasts and human gastric cancer MGC-803 cells was evaluated using an indirect co-culture model in vitro. Results: A high level of fibroblast activation protein (FAP) in the invasion front of gastric cancer was found in the gastric cancer tissue samples and no FAP expression was found in 20 normal gastric tissue samples by immunohistochemistry. High FAP expression was associated with Lauren classification, degree of differentiation, tumour node metastasis stage and depth of tumour invasion (p<0.05 or p<0.01). INFs promoted invasion and migration of MGC-803 cells. The number of invasions in INFs, CAFs and NFs were 120.10±27.53 (95% CI 102.12 to 138.10), 63.00±14.80 (95% CI 53.33 to 72.67) and 14.22±6.20 (95% CI 10.17 to 18.27), respectively; the number of invasions in INFs were 8.45-fold and 1.89-fold higher than those in NFs and CAFs, respectively (p<0.05). The number of migrations in INFs, CAFs and NFs were 118.00±16.83 (95% CI 107.00 to 129.00), 61.00±16.36 (95% CI 50.31 to 71.69) and 24.00±11.52 (95% CI 16.47 to 31.53), respectively; the number of migration in INFs were 4.91-fold and 1.92-fold higher than those in NFs and CAFs, respectively (p<0.05). INFs also significantly promoted cell proliferation and inhibited apoptosis in MGC-803 cells compared with NFs and CAFs (p<0.05). Conclusions: These findings indicate that INFs exhibit a more robust biological modulatory activity than CAFs and NFs. INFs may be a key factor leading to tumour progression and metastasis and may be of use as a tool for post-treatment surveillance.